Pengendalian Kualitas Produk Menggunakan Pendekatan Statistical Process Control (SPC) dan Six Sigma pada Pabrik Tahu Pak Gino - Anjab Muaafii; Cahyani Windarto; Febrina Agusti (Jurnal Teknik Industri Terintegrasi (JUTIN), 2026)
Pak Gino Tofu Factory in Wonogiri still experiences product quality problems, including defects in shape, texture, color, and taste, which may reduce product quality and customer satisfaction. This study aims to analyze product defects, identify their causes, and propose improvements using Statistical Process Control (SPC) and Six Sigma. A mixed-methods approach was employed. SPC analysis utilized check sheets, P-Charts, Pareto charts, and fishbone diagrams, while the Six Sigma approach followed the DMAIC framework. Root causes were analyzed using the 5 Whys method, and improvement priorities were determined through Failure Mode and Effects Analysis (FMEA). The results show that shape defects were the most dominant, followed by texture, taste, and color defects. The main causes were related to human factors, methods, materials, machines, and the work environment. Proposed improvements include developing SOPs, providing operator training, strengthening process supervision, improving raw material control, and conducting regular equipment maintenance to reduce defects and improve product quality.